Complex systems model of fatigue: integrative homoeostatic control of peripheral physiological systems during exercise in humans. Issue 1 (23rd December 2004) - Lambert, E V; St Clair Gibson, A; Noakes, T D
Abstract : Fatigue is hypothesised as being the result of the complex interaction of multiple peripheral physiological systems and the brain. In this new model, all changes in peripheral physiological systems such as substrate depletion or metabolite accumulation act as afferent signallers which modulate control processes in the brain in a dynamic, non-linear, integrative manner.